Shark-related injuries in Hawai’i treated at a level 1 trauma center - Elliott R Haut; Victoria A Scala; Michael S Hayashi; Jason Kaneshige; Karen Ng; Sho Furuta (Trauma Surgery & Acute Care Open)
Background Although rare, human–shark interactions can result in a wide spectrum of injuries. This is the first study to characterize shark-related injuries (SRIs) in Hawai’i.Methods This is a retrospective review of the State of Hawai’i Division of Aquatic Resources Shark Incidents List between January 1, 2009 and December 31, 2019. Trauma registry data and medical records of patients treated for SRIs at the only level 1 trauma center in Hawai’i were reviewed.Results Sixty-one patients sustained SRIs in the Hawaiian Islands: 25 in Maui, 16 in O’ahu, 12 in Hawai’i, and 8 in Kaua’i. In cases where the shark species could be identified, tiger sharks were the most frequent (25, 41%). Four cases were fatal—all died on scene in Maui with the shark species unknown. Forty-five survivors (79%) received definitive care at regional facilities. Twelve (21%) were treated at the level 1 trauma center, of which two were transferred in for higher level of care. Of the 12 patients, 11 (92%) had extremity injuries, with 3 lower extremity amputations (25%), 2 with vascular injuries (17%), and 5 with nerve injuries (42%). One had an injury to the abdomen. All patients had local bleeding control in the prehospital setting, with 9 (75%) tourniquets and 3 (25%) hemostatic/pressure dressings applied for truncal or proximal extremity injuries. The mean time from injury to emergency department arrival was 63 minutes.Discussion Most SRIs are managed at regional facilities, rather than at a level 1 trauma center. Prehospital hemorrhage control is an important survival skill as time to definitive care may be prolonged. For cases treated at the level 1 trauma center, nerve injuries were common and should be suspected even in the absence of major vascular injury. Correlating shark behavior with observed injury patterns may help improve public awareness and ocean safety.Level of evidence Level V, epidemiological.